The Effects of Rosella Extract (Hibiscus sabdariffa) against the n-carboxymethyl-lysine, NF-κβ, TNF-α in the Rats Heating Food Diets - Bataif, Batmomolin; Soeharto K, Setyawati; Widjajanto, Edi; Ratna, Ardhiyanti Puspita; Amalia, Silvy (The Journal of Experimental Life Science, 2018)
The food processing by heating can increase the formation of AGEs (Advanced Glycation End Products). AGEs are compounds that formed from a non-enzymatic continuous glycation reaction between proteins and sugar residues. The CML (N-carboxymethyl-lysine) is used as a marker for AGEs cause most commonly found in vivo. The bond of AGEs and RAGE (receptor for AGEs) induce various signaling pathways that trigger inflammation and increase oxidative stress. The AGE and RAGE interaction activate the transcription factor of NF- κβ. NF- κβactivates gene transcription to release proinflammatory cytokines such as TNF-α. Anthocyanins are compounds that can prevent the formation of AGEs and muffle the adverse effects of AGEs. Rosella contains anthocyanin such as: delphinidin-3-O-glucoside, delphinidin-3-O-sambubioside, and cyanidin-3-O-sambubioside. This study is to determine whether the daily intake of Rosella extract can reduce the levels of n-carboxymethyl-lysine in serum, expression of NF-κβ and TNF α in the rats fed with heated food. This study applied experimental post test control using Rattus norvegicus Wistar strain. The samples were divided into 5 groups: KN (negative control/fed without heating), KP (positive control/fed heated food but not treated by Rosella extract), R1 (fed heated food and treated by 200 mg.kg-1BW Rosella extract), R2 (fed heated food and treated by 300 mg.kg-1BW Rosella extract), and R3 (fed heated food and treated by 400 mg.kg-1BW Rosella extract). The n-carboxymethyl-lysine levels were measured by using the ELISA, the expression of NF-κβ is analyzed by using immunofluorescence, and expression of TNF - α is observed by immunohistochemistry. There was significantly decreased the levels of n-carboxymethyl-lysine in all groups which were treated by Rosella extracts (R1,R2,R3); p= 0.000, α = 0.05 (p< α). Decreased activation of NF-κβ in all groups which were treated by Rosella extract is significant (p = 0.000), and decreased expression of TNF α in all groups which were treated by Rosella extract is also significant (p = 0.000). Rosella extract can reduce the levels of n-carboxymethyl-lysine, expression of NF-κβ, and TNF α. Keywords: AGEs, anthocyanin, Rosella flower extract, n-carboxymethyl-lysine, NF-κβ, TNF α.